Holographic Smart EM Skins for Advanced Beam Power Shaping in Next Generation Wireless Environments - Oliveri, Giacomo; Rocca, Paolo; Salucci, Marco; Massa, Andrea (IEEE journal on multiscale and multiphysics computational techniques, 2021)
An innovative approachfor the synthesis of inexpensive holographic smart electromagnetic (EM) skins with advanced beamforming features is proposed. The complex multi-scale smart skin design is formulated within the Generalized Sheet Transition Condition (GSTC) framework as a combination of a mask-constrained isophoric inverse source problem and a micro-scale susceptibility dyadic optimization. The solution strategy integrates a local search procedure based on the iterative projection technique (IPT) and a System-by-Design(SbD)-based optimization loop for the identification of optimal metasurface descriptors matching the desired surface currents. The performance and the efficiency of the proposed approach are assessed in a set of representative numerical test cases concerned with different smart skin apertures and target pattern masks.